Two-Way Anova for the Study of Revenue Mobilization Inequalities - Darkwah, Kwaku F.; Tawiah, Richard; Adu-Gyamfi, Maxwell (Lithuanian Journal of Statistics, 2015)
The Ghanaian informal sector is characterized by underemployment, bad working conditions, uncertain workrelationships and low earnings. This sector employs 80% of the workforce. Consequently, establishing an efficient tax systemthat can raise sufficient revenue to finance essential expenditures without recourse to government borrowing has been achallenge. Using time series data extracted from a revenue mobilization unit in Ghana, this paper examines the inequalities infour revenue mobilization instruments, namely self-employed tax, company tax, Pay As You Earn (PAYE) tax andmiscellaneous taxes. The study uses the theory of two-way ANOVA as the main approach for exploring the differences. Weassessed the adequacy of our theoretical approach using numerical methods. Revenues generated from the mobilizationinstruments differed significantly with exception of self-employed tax and company tax. Generally, revenue from company,self-employed and miscellaneous taxes were low, compared to Pay As You Earn (PAYE) tax. This study draws attention tothe importance of enhancing the informal sector in order to improve revenue from self-employed tax.